Hepatic Abscess in Preterm Newborn- A rare entity - Anand, Shweta; Chanchlani, Roshan; Gupta, V.; Goyal, Shweta; Tiwari, A. (International Journal of Medical Research and Review, 2014)
Neonatal liver abscess is rare entity and few cases are reported till date. We report a case of newborn who presented with a abdominal lump and a huge liver abscess. Baby underwent Ultrasonography and CT scan and abscess was aspirated under USG guidance. As there was no resolution patient underwent surgical procedure with insertion of pigtail catheter under anaesthesia in operation theatre. Baby is asymptomatic with no residual abscess on follow- up. The patient was managed well with coordination from Paediatric, Radiology and Paediatric surgery department.